Creating Galaxies on a PC - (:unkn) unknown (My University, 2000)
It is shown that galactic simulation does not require a supercomputer. The capacity of new PCs is enough to simulate an N-body system with the number of bodies sufficient to see a galaxy formation from chaos to a disk with a spiral galactic structure. Naturally, simula tions with millions of bodies realized on paral lel supercomputers provide more realistic im ages. However, the number of bodies is not a crucial factor if rather qualitative results are expected. By simulating a pure gravitational system with only 500 particles on a PC, one can observe a fascinating history of a galaxy evolution. Some algorithms for N-body inte gration are discussed and an implementation af a simple "neighbor and far interactions" algorithm is presented. The complete history of a simulated galaxy is shown, including the initial collapse, expansion, formation of the early cloud with rotational movement and, finally, a spiral structure.